Martial and the fiscus Iudaicus Once More - Zeichmann, Christopher B. (Journal for the study of the pseudepigrapha, 2015)
That the fiscus Iudaicus was used to fund the Roman temple known as Jupiter Capitolinus is a commonly accepted fact in social histories of Judaism during the Principate. After discussing the tenuous evidentiary basis for this claim, this article suggests an additional datum in its favor. Namely, one of Martial's epigrams (11.94) makes a peculiar reference to the temple of the ‘Thunderer’ that may be previously unrecognized evidence for the temple's funding.